INTERNATIONAL LOANS AS WAY OF MODERNIZATION OF INFRASTRUCTURE OF THE COUNTRY: BENEFITS AND THREATS (Regional aspects of productive forces development of Ukraine, 2019)
The problem of the prospects of using international credit resources for modernizing the country’s infrastructure is discussed in the article. As the example the water supply and sewage system of enterprise «Novovolynskvodokanal» Volyn region under the Second Urban Infrastructure Project is taken.